Proboszczowie parafii św. Wawrzyńca w Biegonicach w okresie staropolskim. Przyczynek do dziejów duchowieństwa Sądecczyzny - Smoła, Marek (Saeculum Christianum. Pismo Historyczne, 2020)
The article discusses issues related to the history of St. Lawrence parish in Biegonice in the Old-Polish period, through the prism of the clergy holding the office of parish priest. Thanks to a thorough scientific query in numerous archives, it was possible to identify a total of 29 clergymen holding the office of parson in Biegonice. Through thorough research, some additional data were obtained about some of them, thanks to which the community of the pastors was analysed in terms of their geographical and social origin, education, and other functions held in the Church - prelates, canons, court officials and confessors for the convent of the Poor Clares in Stary Sącz. The conclusions will permit a better comprehension of the conditions related to the clergy in the broadly understood area of the Sącz region in the Old-Polish period.